Thermal modeling of automated fiber placement (AFP) of thermoplastic composites using plug flow simulation - Ganesan, Vishnu V.; Smeets, Mark; Amgai, Sandesh; Davidson, Paul; Jain, Ankur (Composites. Part A, Applied science and manufacturing, 2026)
Thermal evolution in material under Automated Fiber Placement (AFP) processing conditions is critical in determining the final microstructure, interface bonding and, consequently, the mechanical properties of the built structure. Thermal modeling offers an important tool to predict the temperature field during AFP laydown and its dependence on various process parameters. This study presents an experimentally-validated heat transfer simulation model of AFP manufacturing of a thermoplastic composite tow. The precise tow geometry and trajectory, as well as its thermal interactions with the roller and substrate are modeled. In order to simulate tow motion past the heat source, the tow and substrate are treated as moving media with distinct plug flow velocities passing through a stationary experimentally measured irradiance field. The governing equations are derived from steady-state advection–diffusion principles, incorporating temperature-dependent anisotropic thermophysical properties. Model predictions are shown to agree well with experimental measurements carried out under simplified process conditions. Lamp power and laydown speed are both shown to impact the temperature history of the tow. Thermal diffusion into the roller is found to significantly influence tow temperature history. Heating of the roller is proposed as a mechanism for controlling how the tow temperature evolves over time. This novel simulation technique captures several realistic considerations in AFP manufacturing that were not fully accounted for by previously reported simulation models. By predicting the temperature field in realistic settings, this work offers a robust framework for predicting thermal performance, and, hence, material properties of parts printed by AFP and other advanced manufacturing techniques.